ANALISIS FITOKIMIA TUMBUHAN OBAT DI KABUPATEN MINAHASA UTARA - Sangi, Meiske; Runtuwene, Max R. J.; Simbala, Henry E. I.; Makang, Veronica M. A. (Sam Ratulangi University, 2008)
A research has been done to analyze the phytochemical of medicine plant used by North Minahasa society. The research done qualitatively to know the present of alkaloid component, flavonoid, triterpenoid, steroid, saponin, and tannin. Analyzes of alkaloid component using Mayer, Dragendorff and Wagner reagents showed presipitate when react with alkaloid. Mayer reagent showed white presipitate, Dragendorff reagent showed red-orange presipitate and Wagner reagen showed brown presipitate. In flavonoid analysis, positive result indicated with red solution. Saponim analysis indicated with a stable foam. Tannins analysis indicated with green and blue-black solution and triterpenoid analysis indicated with red-orange or purple solution. Although the steroida analysis indicated with blue solution. The result show that 46 samples from 46 spesies of medicine plant that had been analyzed are 97,83% positive containing alkaloid component; 13,04% containing triterpenoid; 28,26% containing steroid; 47,83% containing flavonoid; 63,04% containing saponin and 63,44% containing tannin.